qanda-logo
search-icon
Symbol

Calculator search results

Solve the system of equations
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
Graph
$0.2 x - 0.3 y = - 1$
$0.4 x - 5 y = 6.8$
$x$Intercept
$\left ( - 5 , 0 \right )$
$y$Intercept
$\left ( 0 , \dfrac { 10 } { 3 } \right )$
$x$Intercept
$\left ( 17 , 0 \right )$
$y$Intercept
$\left ( 0 , - \dfrac { 34 } { 25 } \right )$
$x = - 8 , y = - 2$
Solve the system of equations
$\begin{cases} \color{#FF6800}{ 0.2 } \color{#FF6800}{ x } - 0.3 y = - 1 \\ 0.4 x - 5 y = 6.8 \end{cases}$
$ $ Calculate the multiplication expression $ $
$\begin{cases} \color{#FF6800}{ \dfrac { \color{#FF6800}{ x } } { \color{#FF6800}{ 5 } } } - 0.3 y = - 1 \\ 0.4 x - 5 y = 6.8 \end{cases}$
$\begin{cases} \dfrac { x } { 5 } \color{#FF6800}{ - } \color{#FF6800}{ 0.3 } \color{#FF6800}{ y } = - 1 \\ 0.4 x - 5 y = 6.8 \end{cases}$
$ $ Calculate the multiplication expression $ $
$\begin{cases} \dfrac { x } { 5 } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { \color{#FF6800}{ 3 } \color{#FF6800}{ y } } { \color{#FF6800}{ 10 } } } = - 1 \\ 0.4 x - 5 y = 6.8 \end{cases}$
$\begin{cases} \dfrac { x } { 5 } - \dfrac { 3 y } { 10 } = - 1 \\ \color{#FF6800}{ 0.4 } \color{#FF6800}{ x } - 5 y = 6.8 \end{cases}$
$ $ Calculate the multiplication expression $ $
$\begin{cases} \dfrac { x } { 5 } - \dfrac { 3 y } { 10 } = - 1 \\ \color{#FF6800}{ \dfrac { \color{#FF6800}{ 2 } \color{#FF6800}{ x } } { \color{#FF6800}{ 5 } } } - 5 y = 6.8 \end{cases}$
$\begin{cases} \dfrac { x } { 5 } - \dfrac { 3 y } { 10 } = - 1 \\ \dfrac { 2 x } { 5 } - 5 y = \color{#FF6800}{ 6.8 } \end{cases}$
$ $ Convert decimals to fractions $ $
$\begin{cases} \dfrac { x } { 5 } - \dfrac { 3 y } { 10 } = - 1 \\ \dfrac { 2 x } { 5 } - 5 y = \color{#FF6800}{ \dfrac { \color{#FF6800}{ 34 } } { \color{#FF6800}{ 5 } } } \end{cases}$
$\begin{cases} \dfrac { x } { 5 } - \dfrac { 3 y } { 10 } = - 1 \\ \dfrac { 2 x } { 5 } - 5 y = \dfrac { 34 } { 5 } \end{cases}$
$ $ Solve a solution to $ x$
$\begin{cases} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { \color{#FF6800}{ 3 } } { \color{#FF6800}{ 2 } } } \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \\ \dfrac { 2 x } { 5 } - 5 y = \dfrac { 34 } { 5 } \end{cases}$
$\begin{cases} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { \color{#FF6800}{ 3 } } { \color{#FF6800}{ 2 } } } \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \\ \color{#FF6800}{ \dfrac { \color{#FF6800}{ 2 } \color{#FF6800}{ x } } { \color{#FF6800}{ 5 } } } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ y } = \color{#FF6800}{ \dfrac { \color{#FF6800}{ 34 } } { \color{#FF6800}{ 5 } } } \end{cases}$
$ $ Substitute the given $ x $ value into the equation $ \dfrac { 2 x } { 5 } - 5 y = \dfrac { 34 } { 5 }$
$\color{#FF6800}{ \dfrac { \color{#FF6800}{ 2 } \left ( \color{#FF6800}{ \dfrac { \color{#FF6800}{ 3 } } { \color{#FF6800}{ 2 } } } \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \right ) } { \color{#FF6800}{ 5 } } } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ y } = \color{#FF6800}{ \dfrac { \color{#FF6800}{ 34 } } { \color{#FF6800}{ 5 } } }$
$\color{#FF6800}{ \dfrac { \color{#FF6800}{ 2 } \left ( \color{#FF6800}{ \dfrac { \color{#FF6800}{ 3 } } { \color{#FF6800}{ 2 } } } \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \right ) } { \color{#FF6800}{ 5 } } } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ y } = \color{#FF6800}{ \dfrac { \color{#FF6800}{ 34 } } { \color{#FF6800}{ 5 } } }$
$ $ Solve a solution to $ y$
$\color{#FF6800}{ y } = \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
$\color{#FF6800}{ y } = \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
$ $ Substitute the given $ y $ value into the equation $ x = \dfrac { 3 } { 2 } y - 5$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { \color{#FF6800}{ 3 } } { \color{#FF6800}{ 2 } } } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) \color{#FF6800}{ - } \color{#FF6800}{ 5 }$
$x = \color{#FF6800}{ \dfrac { \color{#FF6800}{ 3 } } { \color{#FF6800}{ 2 } } } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) - 5$
$ $ Calculate the product of rational numbers $ $
$x = \color{#FF6800}{ - } \color{#FF6800}{ 3 } - 5$
$x = \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ - } \color{#FF6800}{ 5 }$
$ $ Find the sum of the negative numbers $ $
$x = \color{#FF6800}{ - } \color{#FF6800}{ 8 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 8 }$
$ $ The possible solutions are as follows $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 8 } , \color{#FF6800}{ y } = \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 8 } , \color{#FF6800}{ y } = \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
$ $ Check if it is the solution to the system of equations $ $
$\begin{cases} \color{#FF6800}{ 0.2 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 8 } \right ) \color{#FF6800}{ - } \color{#FF6800}{ 0.3 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \\ \color{#FF6800}{ 0.4 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 8 } \right ) \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) = \color{#FF6800}{ 6.8 } \end{cases}$
$\begin{cases} \color{#FF6800}{ 0.2 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 8 } \right ) \color{#FF6800}{ - } \color{#FF6800}{ 0.3 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \\ \color{#FF6800}{ 0.4 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 8 } \right ) \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) = \color{#FF6800}{ 6.8 } \end{cases}$
$ $ Simplify the equality $ $
$\begin{cases} \color{#FF6800}{ - } \color{#FF6800}{ 1 } = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \\ \color{#FF6800}{ \dfrac { \color{#FF6800}{ 34 } } { \color{#FF6800}{ 5 } } } = \color{#FF6800}{ \dfrac { \color{#FF6800}{ 34 } } { \color{#FF6800}{ 5 } } } \end{cases}$
$\begin{cases} \color{#FF6800}{ - } \color{#FF6800}{ 1 } = \color{#FF6800}{ - } \color{#FF6800}{ 1 } \\ \color{#FF6800}{ \dfrac { \color{#FF6800}{ 34 } } { \color{#FF6800}{ 5 } } } = \color{#FF6800}{ \dfrac { \color{#FF6800}{ 34 } } { \color{#FF6800}{ 5 } } } \end{cases}$
$ $ Since it is true in both equations, it is the solution of the system of equations $ $
$\color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ 8 } , \color{#FF6800}{ y } = \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
check-iconSearch by problem image
check-iconAsk 1:1 question to TOP class teachers
check-iconAI recommend problems and video lecture